Monitoring of Social Clauses in the Democratic Republic of Congo 2011-2020 - Tsanga, R.; Cerutti, P.O.; Njumboket, I.; Tibaldeschi, P. (Center for International Forestry Research, 2021)
The social clause system has its origins in (oral or, more rarely, written) agreements that forestry companies in the Congo Basin made with local communities living in the vicinity of the areas where they formerly had operating licences or permits. This system existed long before forestry laws – adopted after the 1992 Rio Summit – institutionalized the practice, inspired by the idea of financing local development through exploiting natural resources. The approach involves promoting social forestry within the broader concept of sustainable management; specifically, using financial contributions from forest concession holders to implement an adopted forest management plan.